2016
DOI: 10.1109/jtehm.2016.2570219
|View full text |Cite
|
Sign up to set email alerts
|

Optical Cryoimaging Reveals a Heterogeneous Distribution of Mitochondrial Redox State in ex vivo Guinea Pig Hearts and its Alteration during Ischemia and Reperfusion

Abstract: Oxidation of substrates to generate ATP in mitochondria is mediated by redox reactions of NADH and FADH2. Cardiac ischemia and reperfusion (IR) injury compromises mitochondrial oxidative phosphorylation. We hypothesize that IR alters the metabolic heterogeneity of mitochondrial redox state of the heart that is only evident in the 3-D optical cryoimaging of the perfused heart before, during, and after IR. The study involved four groups of hearts: time control (TC: heart perfusion without IR), global ischemia (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Our previous study showed increased reactive oxygen species (ROS) in cultured Tmem135 TG fibroblasts [ 11 ], which may be also increased in the Tmem135 TG heart. Using optical cryo-imaging [ 23 25 ], we examined the redox state of the Tmem135 TG heart ( Fig 5 ). This method detects changes in the oxidation state of mitochondrial metabolic coenzymes NADH (NAD in the reduced form) and FAD (FADH 2 in its oxidized form), and provides a quantitative marker for oxidative stress (the ratio of NADH/FAD; the redox ratio) in tissues [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed increased reactive oxygen species (ROS) in cultured Tmem135 TG fibroblasts [ 11 ], which may be also increased in the Tmem135 TG heart. Using optical cryo-imaging [ 23 25 ], we examined the redox state of the Tmem135 TG heart ( Fig 5 ). This method detects changes in the oxidation state of mitochondrial metabolic coenzymes NADH (NAD in the reduced form) and FAD (FADH 2 in its oxidized form), and provides a quantitative marker for oxidative stress (the ratio of NADH/FAD; the redox ratio) in tissues [ 23 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The snap-frozen hearts, stored at −80°C until the day of study, were imaged in our custom-made cryo-imager at the Biophotonics Lab, University of Wisconsin-Milwaukee. We have reported extensively on the cryo-imaging system in previous studies [ 23 25 ]. In brief, a microtome blade sequentially slices the embedded tissue.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The z-sampling was 30 µm, defined by slicing thickness. Freezing, embedding and imaging procedures have been previously described [12,13].…”
Section: Cryoimagingmentioning
confidence: 99%
“…investigation to obtain a real-time information of RR in the tissue [13]. It may offer a stronger utility tool to monitor the liver function at the time of liver transplantation.…”
mentioning
confidence: 99%